Brain Sub/Region-Specific Effects of Olanzapine on c-Fos Expression of Chronically Socially Isolated Rats. (1st January 2019) - Stanisavljević, Andrijana; Perić, Ivana; Gass, Peter; Inta, Dragos; Lang, Undine E.; Borgwardt, Stefan; Filipović, Dragana
Graphical abstract: Highlights: Olz reverses depression- and anxiety-like behaviors induced by CSIS. CSIS increases c-Fos protein expression in stress-relevant brain sub/regions. Olz shows region-specific effects on c-Fos protein expression. Olz in controls shows most pronounced changes if c-Fos protein expression in CPu. Abstract: Olanzapine (Olz) is an atypical antipsychotic used to treat depression, anxiety and schizophrenia, which can be caused by chronic psychosocial stress. c-Fos protein expression has been used as an indirect marker of neuronal activity in response to various forms of stress or pharmacological treatments. We examined the effects of a 3-week treatment of Olz (7.5 mg/kg/day) on c-Fos protein expression in stress-relevant brain sub/regions, its relationship with isolation-induced behavioral changes, and potential sites of Olz action on control and male rats exposed to 6 weeks of chronic social isolation (CSIS), an animal model of depression. Olz treatment reversed depression- and anxiety-like behaviors induced by CSIS and suppressed a CSIS-induced increase in the number of c-Fos-positive cells in subregions of the dorsal hippocampus, ventral (v) DG, retrosplenial cortex, and medial prefrontal cortex. In contrast, no change in c-Fos expression was seen in the CA3v, amygdala and thalamic, hypothalamic or striatal subregions in Olz-treated CSIS rats, suggesting different brain sub/regions' susceptibility to Olz. An increased number of c-Fos-positive cells in the CA1v, amygdala and thalamic, hypothalamic and striatal subregions in controls as well as in the CA1v and subregion of the hypothalamus and nucleus accumbens in Olz-treated CSIS rats was found. Results suggest the activation of brain sub/regions following CSIS that may be involved in depressive and anxiety-like behaviors. Olz treatment showed region-specific effects on neuronal activation. Our data contribute to a better understanding of the mechanisms underlying the CSIS response and potential brain targets of Olz in socially isolated rats.